Multiple threats and conservation opportunities in the forgotten coral rag forests of Zanzibar, Tanzania - Robert Wild; Tim Caro; Nicholas E. Kolarik; Matt Clark; Yussuf Said; Tahir Haji (Biological Conservation, 2026)

Biodiversity Consequences of Replacing Animal Protein From Capture Fisheries With Animal Protein From Agriculture - Duncan Leadbitter; Nicholas J. Aebischer; Neil A. Auchterlonie; Tim G. Benton; Halley E. Froehlich; Stephen Hall; Michel J. Kaiser; Ulrika Palme; Ray Hilborn (Reviews in Fisheries Science & Aquaculture, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Common bottlenose dolphin habitat suitability in Malta's coastal waters as a human-altered environment - Francesca Soster; Charles Galdies; Tim Awbery; Adam Gauci; Benjamin Metzger; Nicholas Barbara; Bruno Díaz López (Marine Environmental Research, 2025)

A Bayesian hierarchical approach to combine interpolation and extrapolation methods for fluvial flux calculation - Fred Worrall; Nicholas J.K. Howden; Tim P. Burt (Journal of Hydrology, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Revival of cryopreserved larvae from the important aquaculture species Pacific White Shrimp (Litopenaeus vannamei) using vitrification and ultra-rapid laser warming - Kieran T. Smith; Kanav Khosla; Guebum Han; Tim Humphrey; Nicholas Phelps; John Bischof (Cryobiology, 2024)

Correction: Improving the communication of multifactorial cancer risk assessment results for different audiences: a co-design process - Francisca Stutzin Donoso; Tim Carver; Lorenzo Ficorella; Nichola Fennell; Antonis C. Antoniou; Douglas F. Easton; Marc Tischkowitz; Fiona M. Walter; Juliet A. Usher-Smith; Stephanie Archer (Journal of Community Genetics, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Improving the communication of multifactorial cancer risk assessment results for different audiences: a co-design process - Francisca Stutzin Donoso; Tim Carver; Lorenzo Ficorella; Nichola Fennell; Antonis C. Antoniou; Douglas F. Easton; Marc Tischkowitz; Fiona M. Walter; Juliet A. Usher-Smith; Stephanie Archer (Journal of Community Genetics, 2024)
Background Multifactorial cancer risk prediction tools, such as CanRisk, are increasingly being incorporated into routine healthcare. Understanding risk information and communicating risk is challenging and healthcare professionals rely substantially on the outputs of risk prediction tools to communicate results. This work aimed to produce a new CanRisk report so users can directly access key information and communicate risk estimates effectively. Methods Over a 13-month period, we led an 8-step co-design process with patients, the public, and healthcare professionals. Steps comprised 1) think aloud testing of the original CanRisk report; 2) structured feedback on the original report; 3) literature review; 4) development of a new report prototype; 5) first round of structured feedback; 6) updating the new report prototype; 7) second round of structured feedback; and 8) finalising and publishing the new CanRisk report. Results We received 56 sets of feedback from 34 stakeholders. Overall, the original CanRisk report was not suitable for patients and the public. Building on the feedback, the new report has an overview of the information presented: section one summarises key information for individuals; sections two and three present information for healthcare professionals in different settings. New features also include explanatory text, definitions, graphs, keys and tables to support the interpretation of the information. Discussion This co-design experience shows the value of collaboration for the successful communication of complex health information. As a result, the new CanRisk report has the potential to better support shared decision-making processes about cancer risk management across clinical settings.

Water hyacinths retain river plastics - Louise J. Schreyers; Tim H.M. van Emmerik; Thanh-Khiet L. Bui; Lauren Biermann; Remko Uijlenhoet; Hong Quan Nguyen; Nicholas Wallerstein; Martine van der Ploeg (Environmental Pollution, 2024)

River plastic transport and storage budget - Louise J. Schreyers; Tim H.M. van Emmerik; Fredrik Huthoff; Frank P.L. Collas; Carolien Wegman; Paul Vriend; Anouk Boon; Winnie de Winter; Stephanie B. Oswald; Margriet M. Schoor; Nicholas Wallerstein; Martine van der Ploeg; et al. (Water Research, 2024)

Multi-amplicon nitrogen cycling gene standard: An innovative approach for quantifying N-transforming soil microbes in terrestrial ecosystems - Christopher J. Gillespie; Tim L. Sit; Althea J. Loucanides; Jialin Hu; Brooke E. Matusko; Nicholas R. Terwilliger; Wei Shi; Samantha M. Steffen; Alex L. Woodley; Shuijin Hu (Soil Biology and Biochemistry, 2024)

Testing for concordance between predicted species richness, past prioritization, and marine protected area designations in the western Indian Ocean - Tim R. McClanahan; Alan M. Friedlander; Julien Wickel; Nicholas A. J. Graham; J. Henrich Bruggemann; Mireille M. M. Guillaume; P. Chabanet; Sean Porter; Michael H. Schleyer; M. Kodia Azali; N. A. Muthiga (Conservation Biology, 2024)
Scientific advances in environmental data coverage and machine learning algorithms have improved the ability to make large‐scale predictions where data are missing. These advances allowed us to develop a spatially resolved proxy for predicting numbers of tropical nearshore marine taxa. A diverse marine environmental spatial database was used to model numbers of taxa from ∼1000 field sites, and the predictions were applied to all 7039 6.25‐km 2 reef cells in 9 ecoregions and 11 nations of the western Indian Ocean. Our proxy for total numbers of taxa was based on the positive correlation ( r 2 = 0.24) of numbers of taxa of hard corals and 5 highly diverse reef fish families. Environmental relationships indicated that the number of fish species was largely influenced by biomass, nearness to people, governance, connectivity, and productivity and that coral taxa were influenced mostly by physicochemical environmental variability. At spatial delineations of province, ecoregion, nation, and strength of spatial clustering, we compared areas of conservation priority based on our total species proxy with those identified in 3 previous priority‐setting reports and with the protected area database. Our method identified 119 locations that fit 3 numbers of taxa (hard coral, fish, and their combination) and 4 spatial delineations (nation, ecoregion, province, and reef clustering) criteria. Previous publications on priority setting identified 91 priority locations of which 6 were identified by all reports. We identified 12 locations that fit our 12 criteria and corresponded with 3 previously identified locations, 65 that aligned with at least 1 past report, and 28 that were new locations. Only 34% of the 208 marine protected areas in this province overlapped with identified locations with high numbers of predicted taxa. Differences occurred because past priorities were frequently based on unquantified perceptions of remoteness and preselected priority taxa. Our environment–species proxy and modeling approach can be considered among other important criteria for making conservation decisions.

A rapid procedure for isotopic purification of copper and nickel from seawater using an automated chromatography system - Xiaopeng Bian; Shun-Chung Yang; Robert J. Raad; Nicholas J. Hawco; Jude Sakowski; Kuo-Fang Huang; Kyeong Pil Kong; Tim M. Conway; Seth G. John (Analytica Chimica Acta, 2024)

Towards reusable building blocks for agent-based modelling and theory development - Uta Berger; Andrew Bell; C. Michael Barton; Emile Chappin; Gunnar Dreßler; Tatiana Filatova; Thibault Fronville; Allen Lee; Emiel van Loon; Iris Lorscheid; Matthias Meyer; Birgit Müller; et al. (Environmental Modelling & Software, 2024)

Predicting marine and aeolian contributions to the Sand Engine’s evolution using coupled modelling - Bart van Westen; Arjen P. Luijendijk; Sierd de Vries; Nicholas Cohn; Tim W.B. Leijnse; Matthieu A. de Schipper (Coastal Engineering, 2024)

A guide to assess the use of gene editing in aquaculture - Nicholas A. Robinson; Tone‐Kari Knutsdatter Østbye; Anne H. Kettunen; Andrew Coates; Luke T. Barrett; Diego Robledo; Tim Dempster (Reviews in Aquaculture, 2024)
Aquaculture creates ‘aquatic foods’ such as fish, shellfish, and seaweeds that are critical for food security. Gene editing using CRISPR‐Cas9 has the potential to transform aquaculture by improving animal welfare, nutritional attributes, and farming efficiency, with benefits for environmental sustainability. However, gene editing also poses risks of harm via side effects on other important traits or genetic introgression into wild populations. Public acceptance of gene edited aquatic species will rapidly erode if risk mitigation is ineffective or not applied. Here, we review the benefits and risks for gene editing in aquaculture. A general framework for risk–benefit analysis of gene editing in aquaculture is proposed, incorporating nine key considerations: genetic impacts, ecological impacts, disease risk mitigation, nature of edit, supply chain environmental footprint, animal welfare, human nutrition, ethical business implications and impacts on local communities. When applied on a case‐by‐case basis, the framework will help identify how gene editing of a farmed species can most enhance production and nutritional benefits while minimising harms to animal welfare, the environment, and society.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Middle Palaeolithic occupation of the southern North Sea Basin: evidence from the Sandscaping sediments emplaced on the beach between Bacton and Walcott, Norfolk, UK - Rob Davis; Nick Ashton; Rachel Bynoe; John Craven; Rob Ferguson; Ian Gardner; Tim Grimmer; Claire Harris; Marcus Hatch; Colin Johnson; Joanne Leonard; Simon Lewis; et al. (Journal of Quaternary Science, 2023)
During the summer of 2019, the Bacton to Walcott Coastal Management Scheme involved the emplacement on to the foreshore of 1.8 million cubic metres of sand and gravel dredged from the submerged sediments of the Palaeo‐Yare in the southern North Sea 11 km off Great Yarmouth. During the following 2‐year period, an active group of collectors identified Palaeolithic artefacts eroding from these sediments, including Levallois cores and flakes, and cordiform handaxes. In this paper, we present an analysis of the lithic artefacts, and consider the relationships between the different elements of the assemblage. We discuss its significance in the context of the Middle Palaeolithic record of northwest Europe and the light it shines on the human occupation of the submerged landscape of the southern North Sea during the later Middle Pleistocene. Interrogation of beach survey data shows the reworking of these sediments to the southeast towards Happisburgh where archaeologically significant exposures of the Cromer Forest‐bed Formation are located. The implications of the introduction of a Middle Palaeolithic assemblage to this stretch of the North Norfolk Coast are considered, highlighting the importance of continuing dialogue between researchers, local authorities and local communities for capturing information and monitoring this critical Palaeolithic resource.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Chemostratigraphic and mineralogical examination of the Kilwa Group claystones, coastal Tanzania: An alternative approach to refine the lithostratigraphy - Ross McCabe; Christopher J. Nicholas; Bill Fitches; David Wray; Tim Pearce (Journal of African Earth Sciences, 2023)

Deep long period seismicity preceding and during the 2021 Fagradalsfjall eruption, Iceland - Tim Greenfield; Tom Winder; Nicholas Rawlinson; John Maclennan; Robert S. White; Thorbjörg Ágústsdóttir; Conor A. Bacon; Bryndís Brandsdóttir; Eva P. S. Eibl; Esme Glastonbury-Southern; Egill Árni Gudnason; Gylfi Páll Hersir; et al. (Bulletin of Volcanology, 2022)
We use a dense seismic network on the Reykjanes Peninsula, Iceland, to image a group of earthquakes at 10–12 km depth, 2 km north-east of 2021 Fagradalsfjall eruption site. These deep earthquakes have a lower frequency content compared to earthquakes located in the upper, brittle crust and are similar to deep long period (DLP) seismicity observed at other volcanoes in Iceland and around the world. We observed several swarms of DLP earthquakes between the start of the study period (June 2020) and the initiation of the 3-week-long dyke intrusion that preceded the eruption in March 2021. During the eruption, DLP earthquake swarms returned 1 km SW of their original location during periods when the discharge rate or fountaining style of the eruption changed. The DLP seismicity is therefore likely to be linked to the magma plumbing system beneath Fagradalsfjall. However, the DLP seismicity occurred ~ 5 km shallower than where petrological modelling places the near-Moho magma storage region in which the Fagradalsfjall lava was stored. We suggest that the DLP seismicity was triggered by the exsolution of CO 2 -rich fluids or the movement of magma at a barrier to the transport of melt in the lower crust. Increased flux through the magma plumbing system during the eruption likely adds to the complexity of the melt migration process, thus causing further DLP seismicity, despite a contemporaneous magma channel to the surface.

Role of Disease Progression Models in Drug Development - Jeffrey S. Barrett; Tim Nicholas; Karim Azer; Brian W. Corrigan (Pharmaceutical Research, 2022)

ESO-ESSO-ESTRO Multidisciplinary Course in Oncology for Medical Students: 4 Years of Experience (2016–2019) - Nicholas Pavlidis; Radoslaw Madry; Marc Peeters; Sergio Sandrucci; Janina Markowska; Fedro Peccatori; Alberto Costa; Jesper Grau Eriksen; Umberto Ricardi; Richard Poetter; Drisk Schrijvers; Jan B. Vermorken; et al. (Journal of Cancer Education, 2022)

Mapping Seafloor Relative Reflectance and Assessing Coral Reef Morphology with EAARL-B Topobathymetric Lidar Waveforms - Nicholas Wilson; Christopher E. Parrish; Tim Battista; C. Wayne Wright; Bryan Costa; Richard K. Slocum; Jennifer A. Dijkstra; Matthew T. Tyler (Estuaries and Coasts, 2022)
Topobathymetric lidar is becoming an increasingly valuable tool for benthic habitat mapping, enabling safe, efficient data acquisition over coral reefs and other fragile ecosystems. In 2014, a novel topobathymetric lidar system, the Experimental Advanced Airborne Research Lidar-B (EAARL-B), was used to acquire data in priority habitat areas in the U.S. Virgin Islands (USVI), spanning the 0–44-m depth range. In this study, new algorithms and procedures were developed for generating seafloor relative reflectance, along with a suite of shape-based waveform features from EAARL-B. Waveform features were then correlated with percent cover of coral morphologies, domed and branched, and total cover of hard and soft corals. Results show that the EAARL-B can be used to produce useful seafloor relative reflectance mosaics and also that the additional waveform shape-based features contain additional information that may benefit habitat classification—specifically, to aid in distinguishing among hard corals and their coral morphologies, domed and branched. Knowing the spatial extent of changes in coral communities is important to the understanding of resiliency of coral reefs under stress from human impacts.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Coastal curios? An analysis of ex situ beach finds for mapping new Palaeolithic sites at Happisburgh, UK - Rachel Bynoe; Nick M. Ashton; Tim Grimmer; Peter Hoare; Joanne Leonard; Simon G. Lewis; Darren Nicholas; Simon Parfitt (Journal of Quaternary Science, 2021)
Recent archaeological discoveries from exposures of the Cromer Forest‐bed Formation at Happisburgh, UK, have radically changed interpretations of the nature and timing of early hominin occupation of northern latitudes, but this in situ archaeology is only one part of the picture. Surface finds of Pleistocene mammalian remains have been found along this coastline for centuries, with stone tools adding to this record over the past 7 years. The ex situ nature of these finds, however, means they are often seen as limited in the information they can provide. This work contributes to a growing body of research from a range of landscape and environmental contexts that seeks to demonstrate the value and importance of these ex situ assemblages. Here the focus is on Palaeolithic flint artefacts and Pleistocene mammalian remains recovered by a group of local collectors through systematic, GPS‐recorded beach collection from 2013 to 2017, and their use in developing a methodology for working with ex situ Palaeolithic finds in coastal locations. The results demonstrate significant patterning that identifies unexplored exposures both onshore and offshore, considerably expanding the known extent of deposits and facilitating new insights into the wider archaeological landscape associated with the earliest occupation of northern Europe.

What We Have Learned From the Framework for Ocean Observing: Evolution of the Global Ocean Observing System - Toste Tanhua; Andrea McCurdy; Albert Fischer; Ward Appeltans; Nicholas Bax; Kim Currie; Brad DeYoung; Daniel Dunn; Emma Heslop; Linda K. Glover; John Gunn; Katherine Hill; et al. (Frontiers in Marine Science, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

A Suite of Field Manuals for Marine Sampling to Monitor Australian Waters - Rachel Przeslawski; Scott Foster; Jacquomo Monk; Neville Barrett; Phil Bouchet; Andrew Carroll; Tim Langlois; Vanessa Lucieer; Joel Williams; Nicholas Bax (Frontiers in Marine Science, 2019)

Passive acoustic monitoring of the decline of Mexico's critically endangered vaquita - Armando Jaramillo‐Legorreta; Gustavo Cardenas‐Hinojosa; Edwyna Nieto‐Garcia; Lorenzo Rojas‐Bracho; Jay Ver Hoef; Jeffrey Moore; Nicholas Tregenza; Jay Barlow; Tim Gerrodette; Len Thomas; Barbara Taylor (Conservation Biology, 2017)
The vaquita (Phocoena sinus) is the world's most endangered marine mammal with approximately 245 individuals remaining in 2008. This species of porpoise is endemic to the northern Gulf of California, Mexico, and historically the population has declined because of unsustainable bycatch in gillnets. An illegal gillnet fishery for an endangered fish, the totoaba (Totoaba macdonaldi) , has recently resurged throughout the vaquita's range. The secretive but lucrative wildlife trade with China for totoaba swim bladders has probably increased vaquita bycatch mortality by an unknown amount. Precise population monitoring by visual surveys is difficult because vaquitas are inherently hard to see and have now become so rare that sighting rates are very low. However, their echolocation clicks can be identified readily on specialized acoustic detectors. Acoustic detections on an array of 46 moored detectors indicated vaquita acoustic activity declined by 80% between 2011 and 2015 in the central part of the species’ range. Statistical models estimated an annual rate of decline of 34% (95% Bayesian credible interval –48% to –21%). Based on results from 2011 to 2014, the government of Mexico enacted and is enforcing an emergency 2‐year ban on gillnets throughout the species’ range to prevent extinction, at a cost of US$74 million to compensate fishers. Developing precise acoustic monitoring methods proved critical to exposing the severity of vaquitas’ decline and emphasizes the need for continual monitoring to effectively manage critically endangered species.

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

Stretch and activation of the human biarticular hamstrings across a range of running speeds - Anthony G. Schache; Tim W. Dorn; Tim V. Wrigley; Nicholas A. T. Brown; Marcus G. Pandy (European Journal of Applied Physiology, 2013)

A fast-track for invasion: invasive plants promote the performance of an invasive herbivore - Tim Engelkes; Nicholas J. Mills (Biological Invasions, 2013)

Electrocorticographic (ECoG) correlates of human arm movements - Nicholas R. Anderson; Tim Blakely; Gerwin Schalk; Eric C. Leuthardt; Daniel W. Moran (Experimental Brain Research, 2012)

A conceptual framework for understanding arthropod predator and parasitoid invasions - Tim Engelkes; Nicholas J. Mills (BioControl, 2011)

Design Factors and Socioeconomic Variables Associated with Ecological Responses to Fishery Closures in the Western Indian Ocean - Tim M. Daw; Joshua E. Cinner; Timothy R. McClanahan; Nicholas A. J. Graham; Shaun K. Wilson (Coastal Management, 2011)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

Extinction vulnerability of coral reef fishes - Nicholas A. J. Graham; Pascale Chabanet; Richard D. Evans; Simon Jennings; Yves Letourneur; M. Aaron MacNeil; Tim R. McClanahan; Marcus C. Öhman; Nicholas V. C. Polunin; Shaun K. Wilson (Ecology Letters, 2011)

Mortality in adult intensive care patients with severe systemic inflammatory response syndromes is strongly associated with the hypo-immune TNF −238A polymorphism - John V. Pappachan; Tim G. Coulson; Nicholas J. A. Child; David J. Markham; Sarah M. Nour; Mark C. K. Pulletz; Matthew J. Rose-Zerilli; Kim de Courcey-Golder; Sheila J. Barton; Ian A. Yang; John W. Holloway (Immunogenetics, 2009)

Prior sprint cycling did not enhance training adaptation, but resting salivary hormones were related to workout power and strength - Blair T. Crewther; Tim Lowe; Robert P. Weatherby; Nicholas Gill (European Journal of Applied Physiology, 2009)

The effect of different warming methods on sensory nerve conduction velocity in shipyard workers occupationally exposed to hand–arm vibration - Martin Cherniack; Anthony J. Brammer; Ronnie Lundstrom; Tim F. Morse; Greg Neely; Tohr Nilsson; Donald Peterson; Esko Toppila; Nicholas Warren; Ulysses Diva; Marc Croteau; Jeffrey Dussetschleger (International Archives of Occupational and Environmental Health, 2008)

Unravelling contamination signals in biogenic silica oxygen isotope composition: the role of major and trace element geochemistry - Tim S. Brewer; Melanie J. Leng; Anson W. Mackay; Angela L. Lamb; Jonathan J. Tyler; Nicholas G. Marsh (Journal of Quaternary Science, 2008)
The oxygen isotope composition of diatom silica ( δ 18 O diatom ) provides valuable information for palaeoclimate studies where carbonate proxies are either rare or absent in many lakes and ocean sediments. Unfortunately, mineral and rock fragments found alongside diatoms in most sediments can be problematic as the method used will liberate oxygen from all components within the sediment, producing both high‐frequency noise and low‐frequency excursions that can resemble climate signals. Removal of mineral contamination to date has largely relied upon the combination of chemical leaching and physical separation techniques (e.g. sieving, density). This combination can be inefficient and often significant proportions of contaminants are present in the ‘purified’ diatom sample. Using electron optical imaging and whole‐rock geochemistry on previously ‘purified’ diatom samples, a mass balance approach has been developed whereby the types and proportions of residual contaminants are identified. By integrating this information with measured oxygen isotope ratios of the contaminants, it is then possible to remove contamination effects from the δ 18 O diatom record. Contamination effects relating to carbonates, tephra and silt are modelled for cores from Lake Tilo (Ethiopia) and Lake Baikal (Siberia). In both lakes the new modelled δ 18 O diatom curves show less high‐frequency noise, thus enabling better resolution of low‐frequency climate signals. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley & Sons Ltd.

Syndromes from segmental vibration and nerve entrapment: observations on case definitions for carpal tunnel syndrome - Martin Cherniack; Anthony J. Brammer; Ronnie Lundstrom; Tim F. Morse; Greg Neely; Tohr Nilsson; Donald Peterson; Esko Toppila; Nicholas Warren; Ulysses Diva; Marc Croteau; Jeffrey Dussetschleger (International Archives of Occupational and Environmental Health, 2008)

Lag Effects in the Impacts of Mass Coral Bleaching on Coral Reef Fish, Fisheries, and Ecosystems - NICHOLAS A. J. GRAHAM; SHAUN K. WILSON; SIMON JENNINGS; NICHOLAS V. C. POLUNIN; JAN ROBINSON; JUDE P. BIJOUX; TIM M. DAW (Conservation Biology, 2007)
Recent episodes of coral bleaching have led to wide‐scale loss of reef corals and raised concerns over the effectiveness of existing conservation and management efforts. The 1998 bleaching event was most severe in the western Indian Ocean, where coral declined by up to 90% in some locations. Using fisheries‐independent data, we assessed the long‐term impacts of this event on fishery target species in the Seychelles, the overall size structure of the fish assemblage, and the effectiveness of two marine protected areas (MPAs) in protecting fish communities. The biomass of fished species above the size retained in fish traps changed little between 1994 and 2005, indicating no current effect on fishery yields. Biomass remained higher in MPAs, indicating they were effective in protecting fish stocks. Nevertheless, the size structure of the fish communities, as described with size‐spectra analysis, changed in both fished areas and MPAs, with a decline in smaller fish ( 45 cm). We believe this represents a time‐lag response to a reduction in reef structural complexity brought about because fishes are being lost through natural mortality and fishing, and are not being replaced by juveniles. This effect is expected to be greater in terms of fisheries productivity and, because congruent patterns are observed for herbivores, suggests that MPAs do not offer coral reefs long‐term resilience to bleaching events. Corallivores and planktivores declined strikingly in abundance, particularly in MPAs, and this decline was associated with a similar pattern of decline in their preferred corals. We suggest that climate‐mediated disturbances, such as coral bleaching, be at the fore of conservation planning for coral reefs.

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

High-resolution comparative physical mapping of mouse Chromosome 10 in the region of homology with human Chromosome 21 - Susan E. Cole; Tim Wiltshire; Elizabeth E. Rue; Dwight Morrow; Phil Hieter; Christina Brahe; Elizabeth M. Fisher; Nicholas Katsanis; Roger H. Reeves (Mammalian Genome, 1999)

The 1976-77 Climate Shift of the Pacific Ocean - Arthur Miller; Daniel Cayan; Tim Barnett; Nicholas Graham; Josef Oberhuber (Oceanography, 1994)